The Impact of Problem-Based Learning Learning Methods on the Development of Islamic Education Learning - Posman Rambe; Nurwahidah Nurwahidah (Yayasan Insan Mulia Bima, 2023)
Students are objects that must be continuously strived to be given a learning climate that can help them be sensitive to their ever-changing environment. This requires teachers to provide learning designs that support this reality. This study aims to reveal the impact that has arisen in the development of PAI learning using the problem-basic learning method. This research is library research, where data is obtained using documentation techniques. The results of this study show that the development of PAI learning using the problem-based learning method will bring out several impacts on students. First, students can develop critical thinking and problem-solving skills independently or with social problems. Second, students are motivated to learn. Third, transferring knowledge to new situations. Fourth, bring out students' creativity in disclosing the investigation of the problem that he is doing.